Interrelation of tense and condition in the taxis field - Altayeva, Almagul; Abdibek Amirov, Raya Darmenkulova,; Seitbekova, Ainur (Opción, 2019)
The purpose of this article is to consider the functional aspect of taxis in Kazakh language, which is included in the Turkic language group. To achieve this goal we have used linguistic analysis and generalized experience on this issue. As a result, functional grammar is investigated from various angels of interchange with the environment: with its function in language, functional activity laws. In conclusion, taxis is a semantic position of language units (phonemes, morphemes, words, phrases) in a linear sequence that their position depends on semantic, emotional and grammatical characteristics of the sentence.